Exploration of Environmental Literacy in the Kampung Warna-Warni Jodipan Malang as a Source of Learning for Biology - Intan Nurul Qomariansyah; H. Husamah; Fuad Jaya Miharja (IKIP Mataram, 2023)
This research aims to analyze the environmental literacy of the community in Kampung Warna-warni Jodipan (KWJ). Environmental literacy is conducted to determine the community's ability to understand and maintain the environment to ensure its balance and prevent pollution. Knowledge and attitudes are important aspects used to measure environmental literacy. This research was conducted on KWJ community involving 83 people as research samples. Data were collected through questionnaires, interviews, and observations using Google Form. Data analysis used Guttman Scale and Likert Scale. The results of data analysis according to the Guttman Scale with a moderate score range (11-16) showed that the community's knowledge is not yet fully maximal in understanding environmental literacy, but with KWJ, the attitudes shown by the community begin to emerge to maintain and preserve their environment. The results of this research can be used as a learning resource for biology in high school class X. This research can be used as a step to improve understanding of environmental literacy.